Peran Pendidikan Agama Islam Dalam Membentuk Karakter Religius Mahasiswa - ‘Afuwah, Rifa (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Students' religious character in higher education is greatly influenced by Islamic Religious Education. The purpose of this study is to shed more light on how Islamic Religious Education influences students' religious identities. This study uses a qualitative methodology in conjunction with a survey of the literature, gathering data from books, journal articles, conference papers, theses, and other sources that are relevant to the subject under investigation. The results of the study show that Islamic Religious Education improves students' comprehension of Islamic teachings, fortifies their spiritual awareness, and fosters moral behavior in everyday life. The approach used to shape the religious character of students includes exemplification, discipline development, habituation, and the creation of a supportive environment. Additionally, students engaging in religious practices, such as prayer, memorization of the Quran, and participation in religious studies, are believed to contribute to the formation of religious character in students.